2023
DOI: 10.3389/fpsyg.2023.1131837
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in competitiveness and fear of failure help explain why girls have lower life satisfaction than boys in gender equal countries

Abstract: Among 15-year-olds, boys tend to report higher life satisfaction than girls. Recent research has shown that this gender gap tends to be larger in more gender-egalitarian countries. We shed light on this apparent paradox by examining the mediating role of two psychological dispositions: competitiveness and fear of failure. Using data from the 2018 PISA study, we analyze the life satisfaction, competitiveness, and fear of failure of more than 400,000 15-year-old boys and girls in 63 countries with known levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This suggests that female respondents generally felt more burdened by the pandemic measures, which is consistent with other studies [ 83 ] and may indicate that female adolescents rely more on face-to-face contact than male adolescents [ 84 ]. Female respondents were also more likely to fear failure, which is in line with other studies [ 68 , 85 ]. At the same time, they were more likely to express a desire for a happy life in the future.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that female respondents generally felt more burdened by the pandemic measures, which is consistent with other studies [ 83 ] and may indicate that female adolescents rely more on face-to-face contact than male adolescents [ 84 ]. Female respondents were also more likely to fear failure, which is in line with other studies [ 68 , 85 ]. At the same time, they were more likely to express a desire for a happy life in the future.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, they were more likely to express a desire for a happy life in the future. This seems plausible in light of recent research indicating lower life satisfaction among female respondents [65,68,86]. Female respondents were more likely to report health-related concerns about the future.…”
Section: Differences According To Gendermentioning
confidence: 77%
See 1 more Smart Citation
“…Girls enter puberty earlier and gain more fat [ 70 ]. Girls at that age are less satisfied with life, have less desire to compete, and a greater fear of failure than boys; additionally, research has also shown that menstruation, social problems, lack of support, and a poorer environment in girls have a bad effect on PA [ 71 , 72 ]. We assume that since girls enter puberty earlier and mature sooner, they already start questioning their future adult life, while boys of that age are considered immature and still interested in children’s games.…”
Section: Discussionmentioning
confidence: 99%
“…These two indices, HDI and GII are highly positively correlated with each other at the country level, r(191) = -.91 (UNDP, 2022). In some recent studies (Eriksson & Strimling, 2023;Mac Giolla & Kajonius, 2019), a more comprehensive index of gender equality known as the Global Gender Gap Index (World Economic Forum, 2022) has been used which measures economic participation and opportunity, educational attainment, health and survival and political empowerment of women compared to men in a society. The HDI and GGG scores have been shown to be correlated at r = .60 across 62 countries (Bosson et al, 2021).…”
Section: The Aim Of the Studymentioning
confidence: 99%